1996
DOI: 10.1146/annurev.bi.65.070196.002301
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of Lectin-Carbohydrate Recognition

Abstract: Lectins are responsible for cell surface sugar recognition in bacteria, animals, and plants. Examples include bacterial toxins; animal receptors that mediate cell-cell interactions, uptake of glycoconjugates, and pathogen neutralization; and plant toxins and mitogens. The structural basis for selective sugar recognition by members of all of these groups has been investigated by x-ray crystallography. Mechanisms for sugar recognition have evolved independently in diverse protein structural frameworks, but share… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
670
0
14

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,077 publications
(705 citation statements)
references
References 0 publications
21
670
0
14
Order By: Relevance
“…In all cases the combining site appears to be preformed, 35 since few conformational changes occur upon binding. In all legume lectins, irrespective of their specificity, four invariant amino acid residues participate in the ligand binding: an aspartic acid, an asparagine, a glycine (conserved in all the lectins of the family apart from Con A) and an aromatic amino acid 36 or leucine: 37 Asp83, Gly104, Asn127 and Tyr125 for PNA.…”
Section: Structural Featuresmentioning
confidence: 99%
“…In all cases the combining site appears to be preformed, 35 since few conformational changes occur upon binding. In all legume lectins, irrespective of their specificity, four invariant amino acid residues participate in the ligand binding: an aspartic acid, an asparagine, a glycine (conserved in all the lectins of the family apart from Con A) and an aromatic amino acid 36 or leucine: 37 Asp83, Gly104, Asn127 and Tyr125 for PNA.…”
Section: Structural Featuresmentioning
confidence: 99%
“…Several MBPcarbohydrate complex structures, including complexes of MBP with several monosaccharides (11) and in one case with a polysaccharide (12), have been determined by X-ray crystallography. These studies have shown that MBP specifically recognizes vicinal, equatorial OH groups on monosaccharides equivalent to those present at the 3 and 4 positions of sugars such as mannose and glucose (13). It appears that MBP recognizes similar OH groups present on the nonreducing terminal carbohydrate residues of polysaccharides (12).…”
Section: Sp-d Binds Many Microorganisms In Vitromentioning
confidence: 96%
“…Basic residues constitute the basis for link protein-hyaluronate interactions via the PTR domains [47,48], even though proteincarbohydrate interactions might be mediated also by hydrogen bond and hydrophobic contacts [49]. First, electrostatic surface potentials were calculated for mannose-binding protein and Eselectin as a control.…”
Section: Electrostatic Surface Calculations Of the G3 Crd And Scr Dommentioning
confidence: 99%
“…Those involving heparin have been described for basic fibroblast growth factor and antithrombin III, both of which involve an arrangement of four or five basic residues [51,52]. In contrast, a survey of known lectincarbohydrate interactions shows that acidic and amide groups commonly form the basis of hydrogen bond formation between protein and carbohydrate hydroxy groups in complex-type and high-mannose-type oligosaccharides [49]. Although Arg-97 and Lys-113 have been implicated in E-selectin adhesion to neutrophils [17], Arg-97 in that study corresponds to the loop between residues 115 and 116 in Figure 2 and is not conserved in Pselectin, whereas Lys-113 corresponds to residue 128 in Figure 2 and is conserved in the selectins and some of the group III CRDs.…”
Section: Structure Function and Evolution Of G3 In Proteoglycansmentioning
confidence: 99%